A re-evaluation of the final step of vanillin biosynthesis in the orchid Vanilla planifolia. (July 2017) - Yang, Hailian; Barros-Rios, Jaime; Kourteva, Galina; Rao, Xiaolan; Chen, Fang; Shen, Hui; Liu, Chenggang; Podstolski, Andrzej; Belanger, Faith; Havkin-Frenkel, Daphna; Dixon, Richard A.
Abstract: A recent publication describes an enzyme from the vanilla orchid Vanilla planifolia with the ability to convert ferulic acid directly to vanillin. The authors propose that this represents the final step in the biosynthesis of vanillin, which is then converted to its storage form, glucovanillin, by glycosylation. The existence of such a "vanillin synthase" could enable biotechnological production of vanillin from ferulic acid using a "natural" vanilla enzyme. The proposed vanillin synthase exhibits high identity to cysteine proteases, and is identical at the protein sequence level to a protein identified in 2003 as being associated with the conversion of 4-coumaric acid to 4-hydroxybenzaldehyde. We here demonstrate that the recombinant cysteine protease-like protein, whether expressed in an in vitro transcription-translation system, E. coli, yeast, or plants, is unable to convert ferulic acid to vanillin. Rather, the protein is a component of an enzyme complex that preferentially converts 4-coumaric acid to 4-hydroxybenzaldehyde, as demonstrated by the purification of this complex and peptide sequencing. Furthermore, RNA sequencing provides evidence that this protein is expressed in many tissues of V. planifolia irrespective of whether or not they produce vanillin. On the basis of our results, V. planifolia does not appear to contain a cysteine protease-like "vanillin synthase" that can, by itself, directly convert ferulic acid to vanillin. The pathway to vanillin in V. planifolia is yet to be conclusively determined. Graphical abstract: Highlights: Vanilla planifolia extracts have 4-hydroxybenzaldehyde synthase activity. This activity is associated with a cysteine protease-like protein. This protein could not be shown to possess vanillin synthase activity. This protein is constitutively expressed in all V. planifolia tissues tested.